Strengthening Infrastructure Governance for Climate-Responsive Public Investment. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2021)
Countries have committed, through the Paris Agreement and the Sustainable Development Goals (SDGs), to pursue climate targets and policies that would limit global temperature rise to well below 2 degrees Celsius, compared to pre-industrial levels. A shift toward green public investment will help to mitigate greenhouse gas (GHG) emissions. In addition, substantial public investment will be necessary to build public infrastructure that makes economies more resilient to climate change and related natural disasters. Climate change mitigation and adaptation challenges thus compound preexisting needs for public investment to foster the economic recovery from the pandemic and to meet the SDGs in a broader range of areas, often in a context of limited fiscal space. Against this backdrop, a priority for all countries is to manage their public investment efficiently and effectively. To help countries improve the institutions and processes for infrastructure governance (the planning, allocation, and implementation of public investment), the IMF developed in 2015 the Public Investment Management Assessment (PIMA), which has already been applied in over 70 countries. However, the current PIMA does not provide a sufficiently tailored assessment of how public investment management can support climate change mitigation and adaptation. To fill this gap, this paper introduces a new module to the to the current Public Investment Management Assessment (PIMA) framework, the 'Climate-PIMA' (C-PIMA), whose goal is to help governments identify potential improvements in public investment institutions and processes to build low-carbon and climate-resilient infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fiscal Policy, Climate Change and Infrastructure Governance; Monetary Policy; Political Economy; Public Investment Management